1994
DOI: 10.1104/pp.104.4.1277
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of H+-ATPase Activity by Fusicoccin in Plasma Membrane Vesicles from Oat (Avena sativa L.) Roots (A Comparison of Modulation by Fusicoccin, Trypsin, and Lysophosphatidylcholine)

Abstract: l h e funga1 phytotoxin fusicoccin affects various transport processes in the plasma membrane of plant cells. l h e plasma membrane (PM) H+-ATPase (EC 3.6.1.35) seems to be the primary target of fusicoccin action. l h e kinetics of the stimulation of the PM H+-AlPase by fusicoccin was studied in PM vesicles isolated from oat (Avena sativa cv Adamo) roots by aqueous two-phase partitioning. Considerable stimulation of activity was observed only when roots were treated with fusicoccin prior to the PM isolation. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…The activated form of AHA2 was characterized by having increased V max at pH values between 6.8 and 7.5. This kinetic behaviour of the activated AHA2 resembles that of H ϩ -ATPase activated by fusicoccin in planta (Johansson et al, 1993;Lanfermeijer and Prins, 1994;Rasi-Caldogno et al, 1993). Removal of the C-terminal regulatory domain by genetic means results in a similar shift of the pH profile (Regenberg et al, 1995).…”
Section: -3-3 Proteins Activate Plant H ϩ -Atpase Provided Fusicoccmentioning
confidence: 67%
“…The activated form of AHA2 was characterized by having increased V max at pH values between 6.8 and 7.5. This kinetic behaviour of the activated AHA2 resembles that of H ϩ -ATPase activated by fusicoccin in planta (Johansson et al, 1993;Lanfermeijer and Prins, 1994;Rasi-Caldogno et al, 1993). Removal of the C-terminal regulatory domain by genetic means results in a similar shift of the pH profile (Regenberg et al, 1995).…”
Section: -3-3 Proteins Activate Plant H ϩ -Atpase Provided Fusicoccmentioning
confidence: 67%
“…The fungal phytotoxin fusicoccin (FC) 1 activates the plant plasma membrane H ϩ -ATPase by a process involving the Cterminal domain of the pump (6,7). To date it is well established that FC binds to and subsequently stabilizes a complex consisting of the enzyme's C terminus and 14-3-3 proteins (8 -10).…”
mentioning
confidence: 99%
“…As expected, membranes from FC-treated roots showed a stimulation of the vanadate-sensitive, ATP-hydrolysing activity tested at pH 7.4. The stimulation over the control ranged from 50 to 100%, depending on the preparation and the ratio of the ATP-hydrolytic activity between pH 6.5 and 7.4 was 2 for the control and 1 for the FC-activated enzyme [10][11][12]. Interestingly, it was found that during two-phase partitioning the in vivo-bound FC was released (data not shown), so that purified membranes from FC-treated roots were still able to bind [aH]FC.…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been demonstrated that the trypsin-activated H÷-ATPase shows biochemical features very similar to those induced by FC activation [10][11][12], the same purification procedure was also used to solubilise and purify the membranebound, trypsin-activated H+-ATPase. The ratio of its ATPhydrolytic activity at pH 6.5 and 7.4 was compared to that of the H+-ATPase purified from control membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation